2018
DOI: 10.32557/useful-2-4-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic changes in water ecosystem on the example оf the river Tisza.

Abstract: While conducting the ecological estimation of the hydro ecosystems (HE) condition of Tisza water basin, engineering ecological indices and their parameters are used. The system-basin research approach of the water basin based on systematization and data processing of the eco-logical monitoring for a long-term period is used. Such period allowed to set scientific regu-larities of naturally-anthropogenic hydro ecosystems development in the conditions of con-stant anthropogenic load on them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The water of headwaters, which makes up about 99% of the river network of large river basins and suffers an extremely large man-caused impact, provides over 20% of all national economic needs of Ukraine. Modern agricultural land usage does not meet the requirements of rational nature management; the environmental permissible ratio of arable land, natural forage lands, and forest plantations is violated [11,12]. The researches have showed that the greatest influence on the formation of the hydrochemical composition of small water objects in Zhytomyr region is due to factors that depend on the state of the water intake surface and the structure of the water usage intake.…”
Section: Conclusion and Perspectives Of Further Researchesmentioning
confidence: 99%
“…The water of headwaters, which makes up about 99% of the river network of large river basins and suffers an extremely large man-caused impact, provides over 20% of all national economic needs of Ukraine. Modern agricultural land usage does not meet the requirements of rational nature management; the environmental permissible ratio of arable land, natural forage lands, and forest plantations is violated [11,12]. The researches have showed that the greatest influence on the formation of the hydrochemical composition of small water objects in Zhytomyr region is due to factors that depend on the state of the water intake surface and the structure of the water usage intake.…”
Section: Conclusion and Perspectives Of Further Researchesmentioning
confidence: 99%
“…To our mind the only reliable means to prevent migration and accumulation of biogenic toxins consist of in creation a modern methodological base with a broad involvement the data of the natural experiments with the following profounded analysis of its. This requires an in-depth study of the soil processes and the substantiation of the basic soil regimes, the construction of a generalized mathematical models and the development of the methods for calculating regime characteristics, constructive and technological parameters [13,14].…”
Section: Introductionmentioning
confidence: 99%